Powers of Protection The Buddhist Tradition of Spells in the Dhāraṇīsaṃgraha Collections - Hidas, Gergely (Beyond Boundaries, 2021)
This volume explores the most extensive tradition of Buddhist dharani literature and provides access to the earliest available materials for the first time. The Dhāraṇīsaṃgraha collections have been present in South Asia, and especially in Nepal, for more than eight hundred years and served to supply protection, merit and auspiciousness for those who commissioned their compilation.